The effect of 30 to 60 minutes of forced-air pre-warming on maintaining intraoperative core temperatures during the first hour post-anesthesia induction in adult patients undergoing general anesthesia: a systematic review protocol. (April 2016) - Chan, Toi Nei; Venus, Jyothis
Abstract : Review question/objective: The objective of this review is to identify the effectiveness of 30 to 60 minutes of forced-air pre-warming on maintaining intraoperative core temperatures in adult patients undergoing general anesthesia. The review question will focus on the effects of forced-air pre-warming on preventing redistribution hypothermia in the first hour post induction of anesthesia, which is considered the most critical due to an internal core-to-peripheral redistribution of body heat and subsequent loss of heat to the operative room surroundings.